Adsorption study of heavy metals in aqueous solutions aiming at the treatment of contaminated groundwater. Issue 14 (6th December 2019) - Monte Blanco, Silvia Priscila Dias; Scheufele, Fabiano Bisinella; Módenes, Aparecido Nivaldo; Schneider, Karise; de Oliveira, Ana Paula; Paraíso, Paulo Roberto; Bergamasco, Rosângela
Abstract: This study evaluates the application of the vegetal activated carbon (AC), vegetable AC impregnated with Ag and Cu (0.08% m/m) and cationic Supergel TM SGC650H resin for adsorption of Fe 3+ and Pb 2+ ions in closed and batch system. The best adsorption capacities were obtained by using the cationic resin SGC650H, pH 3, temperature of 30 °C and stirring speed of 100 rpm. Thus, the kinetic and equilibrium experiments, in mono- and bicomponent, were performed using SGC650H resin, wherein the kinetic models of pseudo-first and pseudo-second order presented a good fit to the kinetic data, for mono- and bicomponent, respectively. The Langmuir isotherm adequately represented the monocomponent equilibrium data, showing maximum adsorption capacities values of 7.18 and 4.00 meq g −1 for Fe 3+ and Pb 2+, respectively. An inhibitory effect between the metal species was verified by fitting the modified extended Langmuir isotherm model to the binary equilibrium data, which allowed to predict changes in the surface affinity to the adsorbent by the metal ions. Based on the observed results, the use of SGC650H resin presents great potential for water treatment systems contaminated with heavy metals.